Systemic immune-inflammation index as a versatile biomarker in autoimmune disorders: insights from rheumatoid arthritis, lupus, and spondyloarthritis - Wu, Yang; Huang, Yupeng; Wu, Yan; Sun, Jianhong; Xie, Qibing; Yin, Geng (Frontiers in Immunology, 2025)
Autoimmune diseases, such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic vasculitis, spondyloarthritis (SpA), including ankylosing spondylitis (AS) and psoriatic arthritis (PsA), are characterized by chronic immune activation and systemic inflammation. The systemic immune-inflammation index (SII), computed as platelet count × neutrophil count/lymphocyte count, is a promising biomarker that reflects both inflammatory burden and immune dysregulation. In RA, elevation of SII is correlated with disease activity score, response to TNF-α inhibitors, and reduced serum Klotho levels. In AS and PsA, the SII is associated with disease activity scores, musculoskeletal imaging findings, and treatment response. In SLE, the SII tracks global activity and predicts lupus nephritis and pregnancy outcomes, while further reflecting underlying features, such as lymphopenia, neutrophil extracellular trap formation, and platelet activation. The SII is also useful in vasculitis-related diseases, including Behçet’s syndrome and Kawasaki disease. In comparison to traditional markers such as CRP and ESR, the SII provides broader immune insights than routine hematologic data. SII is influenced by non-autoimmune factors, including malignancy and infection, which are often excluded from autoimmune studies, although significant in clinical interpretation. This review summarizes the latest evidence on the SII across autoimmune conditions. It also aims to outline the key limitations and future directions, including longitudinal validation, integration with emerging indices (e.g., the systemic inflammatory response index), and its role in multimodal disease monitoring.